THERAPEUTIC MANAGEMENT OF CHRONIC KIDNEY DISEASE IN DOGS: SUPPORTIVE STRATEGIES AND LONGEVITY (International Seven Journal of Multidisciplinary, 2026)
Chronic kidney disease (CKD) in dogs represents a substantial clinical challenge due to its progressive and irreversible evolution. Traditionally, therapeutic management is based on staging and controlling secondary complications such as hypertension, electrolyte disturbances, and intestinal dysbiosis. However, recent studies support multimodal approaches capable of directly interfering with the pathophysiological mechanisms that drive disease progression. In this scenario, the gut-kidney axis contributes to the morbidity and progression of CKD, becoming a fundamental therapeutic basis. The literature highlights that intestinal dysbiosis promotes the dysregulation of metabolic processes and systemic inflammation, favoring the accumulation of uremic toxins that exacerbate kidney damage. Therefore, strategic dietary management, with controlled protein restriction, increased fiber intake, and supplementation with essential amino acids, proves effective in modulating the microbiota, reducing the uremic load, and preserving lean mass. These strategies are complemented by intestinal microbiota replacement, adsorbents and vitamin D analogs for the control of secondary renal hyperparathyroidism, as well as individualized modulation of the renin-angiotensin-aldosterone system. In parallel, the application of sensitive biomarkers, such as symmetric dimethylarginine (SDMA), allows for early diagnosis and more rigorous monitoring of CKD progression. In short, the integration of personalized interventions is crucial to optimize survival and ensure the quality of life of canine nephropathic patients.